Deriving Wealth from the Dry Matter of Some Under-Utilised Plant Parts - J. E.*, Otoide; S. O., Ihinmikaiye; T. F., Otoide, (International Journal of Scientific Research and Management (IJSRM), 2020)
The possibility of creating wealth in pulp and paper industry from the underutilized dry matters of the leaf sheaths of the pseudostem (Musa paradisiaca and M. sapientum), leaf stalk (Carica papaya) and stems (Panicum maximum and Andropogon tectorum) have been established from the anatomical parameters and indexes (fibre lengths and diameters, lumen width, cell wall thickness, Runkels ratio, flexibility coefficient (%) and slenderness ratio) of the fibres using standard procedures. Results obtained revealed that the Runkels ratio of the fibres in the five dry matters were 0.60, 0.44, 0.40, 0.87 and 0.93 for Musa sapientum, M. paradisiaca, Carica papaya, Panicum maximum and Andropogon tectorum respectively. These values, each been less than 1 (˂ 1) recommends each of the dry matters as suitable alternative source of raw materials for pulp and paper production industry. It was recommended that these dry plant materials be henceforth harnessed as alternative sources of raw materials for pulp and paper production industry as another means of wealth creation instead of allowing them to waste and cause environmental nuisance.